2010
DOI: 10.1371/journal.pmed.1000235
|View full text |Cite
|
Sign up to set email alerts
|

Packages of Care for Attention-Deficit Hyperactivity Disorder in Low- and Middle-Income Countries

Abstract: In the sixth in a series of six articles on packages of care for mental disorders in low- and middle-income countries, Alan Flisher and colleagues discuss the treatment of attention-deficit hyperactivity disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 55 publications
(57 reference statements)
0
33
0
Order By: Relevance
“…Task shifting approaches that build the capacities of a range of care providers in community settings have been successfully adopted and can be instrumental for increasing access to care for individuals with a range of mental disorders in low-resource settings [14],[15]. Evidence on the effectiveness of provision of psychosocial interventions for intellectual disabilities and autism spectrum disorders by non-specialist providers in HICs is emerging [16].…”
Section: Introductionmentioning
confidence: 99%
“…Task shifting approaches that build the capacities of a range of care providers in community settings have been successfully adopted and can be instrumental for increasing access to care for individuals with a range of mental disorders in low-resource settings [14],[15]. Evidence on the effectiveness of provision of psychosocial interventions for intellectual disabilities and autism spectrum disorders by non-specialist providers in HICs is emerging [16].…”
Section: Introductionmentioning
confidence: 99%
“…39 Recent studies have pointed out the necessity of cost-effectiveness studies for LMICs, 40 but, to the best of our knowledge, the present work is the first to show an advantageous economic option for a chronic disease which can be treated with MPH-IR even in low-resource settings. 41 In addition, our study demonstrated that, in LMICs, investments in such analyses can reveal a favorable scenario in contrast with wealthy countries. To illustrate, the incremental cost per QALY gained with MPH-IR treatment seems to be much more attractive for the Brazilian public health system when compared to that of the UK, where the ICER was estimated at I$ 13,904/QALY, 42 or to the U.S. (I$ 18,717/QALY), 43 and even better if compared to atomoxetine treatment in Spain (I$ 43,427/QALY) 19 (original costs were d 9,177, US$ 14,758, and h 34,308, respectively).…”
Section: Discussionmentioning
confidence: 59%
“…In fact, according to international guidelines, combinations of treatment modalities are preferable to medication alone. 41 The main reasons for our choice of MPH-IR could be summarized as: the high costs of extended-release presentations, the absence of a specific policy for ADHD treatment by the Brazilian authorities, 45 and the high costs of adding combined treatments, as demonstrated by the MTA. 17 Lastly, the MPH-IR prices adopted are exclusively for the Brazilian government, which means they are lower than wholesale prices.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating mental health care into existing care systems (e.g., primary care clinics, NGOs, schools) is a pragmatic approach that can maximize the efficiency of resource investments [13, 18, 22, 31, 73]. Understanding mental health systems development is needed to promote translation of research into policy and practice.…”
Section: Global Mental Health: Lessons To Be Learnedmentioning
confidence: 99%